The effect of the beehive strategy on deliberate thinking and learning the setting skill of volleyball among female students at the College of Physical Education and Sports Sciences for Woman - Israa Fouad Salih; Najlaa Abbas AL-Zuhairi; Liza Rustum Yaqoob; Missaa Nadem; Fatima AL-Zahraa IBrahim Beden (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: Develop a deliberate thinking scale for the setting skill in volleyball for second-year female students in the College of Physical Education and Sports Sciences for Woman.